Platelet-rich fibrin in oral surgical procedures: a systematic review and meta-analysis. Issue 3 (March 2019) - Canellas, J.V.d.S.; Medeiros, P.J.D.; Figueredo, C.M.d.S.; Fischer, R.G.; Ritto, F.G.
Abstract: The effect of platelet-rich fibrin (PRF) in enhancing the healing after oral surgical interventions is still a matter of debate. The purpose of this study was to identify instances where PRF has been shown to be effective in oral surgical procedures. A comprehensive literature search was performed up to 2017 on PubMed/MEDLINE, Cochrane Library, Web of Science, Scopus and LILACS databases and grey literature. The full-text of potentially relevant studies were reviewed and only randomized clinical trials (RCTs) were included. A total of 559 studies were found, of which 30 were included for qualitative analysis and 13 for quantitative analysis. Three review authors assessed the risk of bias independently. The available literature suggests that PRF has a positive effect in improving alveolar preservation on extraction sockets and around dental implants. The qualitative analysis showed a significantly better effect of PRF in promoting bone regeneration for alveolar cleft reconstruction. The meta-analysis for third molar surgery showed a decrease in prevalence of alveolar osteitis. PRF increased implant stability 1 week and 1 month after surgery ( P = 0.0005 and 0.0003). Due to the lack of studies with low risk of bias and a limited number of patients available, further RCTs are needed to confirm these results.